Determining of internal factors affecting compliance of pregnant women in Covid-19 vaccination - Devi Permata Sari; Chori Elsera; Sri Sat Titi Hamranani (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2023)
Background:Covid-19 vaccination for pregnant women was an effort to prevent and transmit Covid-19 to pregnant women. Obedience of pregnant women is the behavior of pregnant women in accordance with the guidelines. Compliance of pregnant women in the Covid-19 vaccination is important to study because it is to increase the complete adherence of pregnant women in the Covid-19 vaccination, thereby increasing the immunity of pregnant women. Internal factors that can influence pregnant women's compliance with Covid-19 vaccination include the pregnant woman's age, gestational age, educational status, employment, knowledge, motivation, perception and self- efficacy.Objectives: Analyzing the relationship between maternal age, gestational age, educational status, occupation, income, knowledge, motivation, perception, and self- efficacy with pregnant women's adherence to the Covid-19 vaccination.Analyze the internal factors that most influence the adherence of pregnant women in the Covid-19 vaccination.Methods: The research design used a quantitative descriptive with a cross sectional approach. The population in this study amounted to 86 pregnant women. The sampling technique used quota sampling with a sample of 46 pregnant women. The research instrument uses a questionnaire that has been tested for validity and reliability. Data analysis using Chi Square Test and multiple regression.Results: The results of the study showed that the factor associated with the compliance of pregnant women in the Covid-19 vaccination was gestational age (p value 0.002). Meanwhile, factors that were not related to the compliance of pregnant women in the Covid-19 vaccination were the age of the pregnant mother (p value 0.497), educational status (p value 0.252), occupation (p value 0.829), income (p value 0.605), knowledge (p value 0.351), motivation (p value 0.558), perception (p value 0.295), and self-efficacy (p value 1.000).Conclusions: The conclusion of this study is that the factor that most influences pregnant women's adherence to the Covid-19 vaccination is gestational age with a p- value of 0.005 (a = 0.05) and respondents with a younger gestational age are at risk of0.047 times experiencing non-adherence to Covid-19 vaccination.